Self-leadership strategies on innovative work behaviors among government school teachers - Omar, Intan Marfarrina; Md Sawari, Siti Salwa; Mat Ali, Nor A'tikah (2018)
Innovative work behavior has gained considerable attention in the organizational behavior literature. Research on an integrated framework that cover personal predictors of innovative work behavior is still limited specifally among Malaysia government scholl teachers. This research incorporated the components of an individual’s behavioral (behavior-focused), cognitive (constructive thought pattern and natural reward) and physiological (physical vitality) approach as self-leadership strategies that serve as predictors of innovative work behavior. This research utilized quantitative approach where questionnaires were distributed to 250 government school teachers as the population. 234 completed questionnaires were usable for data analysis. IBM Statistical Package for Social Science 22 statistical program was used to analyze the data. The findings indicated that behaviour-focused strategies, constructive thought pattern strategies, natural reward strategies and physiological strategies significantly affected innovative work behavior of government school teachers. The findings of the study may help organizations to increase teachers’ innovative work behavior by improving teachers’ self-leadership strategies at the workplace.